The Effect of High Dietary Protein Levels During Late Gestation on Colostrum Yield and Lamb Survival Rate in Singleton-Bearing Ewes - Ocak, N.; Çam, M.A.; Kuran, M. (Elsevier Science BV, 2005)
The study was carried out to determine the effect of crude protein (CP) levels in late pregnancy on the subsequent colostrum production and lamb survival rate. A total of 40 singleton-bearing Hampshire Down X Karayaka (F 1) crossbred ewes were allocated to two treatment groups (n=20 for each group), namely a control (P) and high CP (1.4P) group. The ewes in the P group were fed a protein maintenance level for pregnant ewes (117 g CP and 10.5 MJ metabolizable energy (ME)/kg dry matter (DM)), while ewes in the 1.4P group were fed 1.4 times the protein requirement level for pregnant ewes (165 g CP and 10.5 MJ ME/kg DM). The high crude protein level (1.4P) offered to the ewes did not affect lamb body weight from birth to weaning, however, it increased the live weight changes of ewes (2.5±1.3 kg for P versus 6.4±1.5 kg for 1.4P; P<0.05), lambing difficulty (5% versus 30%; χ2=4.33; P<0.05) and lamb birth weight (4.3±0.1 kg versus 4.9±0.1 kg; P<0.05). It also decreased the total colostrum yield (1700±165 g versus 1200±147 g; P<0.01) and lamb survival from birth to weaning (100% versus 80%; χ2=4.44; P<0.05). These results indicate a high level of CP (1.4P) supplementation to singleton-bearing ewes during late gestation to increase lamb birth weight decrease colostrum yield, increase lambing difficulty and reduce lamb survival rate prior to weaning. In conclusion, because of the adverse effect of high dietary protein nutrition during late gestation on colostrum yield and lamb survival rate in singleton-bearing ewes, feeding of protein to pregnant ewes with a view to increase postnatal lamb growth performance and lamb survival rate, should be treated with caution. © 2004 Elsevier B.V. All rights reserved.
Keywords: Newborn; Nutrition; Pregnancy; Reproduction; Sheep